Hybrid Thin-Film Materials Combinations for Complementary Integration Circuit Implementation - Gunhoo Woo; Hocheon Yoo; Taesung Kim (Membranes, 2021)
Beyond conventional silicon, emerging semiconductor materials have been actively investigated for the development of integrated circuits (ICs). Considerable effort has been put into implementing complementary circuits using non-silicon emerging materials, such as organic semiconductors, carbon nanotubes, metal oxides, transition metal dichalcogenides, and perovskites. Whereas shortcomings of each candidate semiconductor limit the development of complementary ICs, an approach of hybrid materials is considered as a new solution to the complementary integration process. This article revisits recent advances in hybrid-material combination-based complementary circuits. This review summarizes the strong and weak points of the respective candidates, focusing on their complementary circuit integrations. We also discuss the opportunities and challenges presented by the prospect of hybrid integration.